Pergeseran Tradisi Samsom dalam Membuka Lahan Perkebunan di Kampung Lilinta, Distrik Misool Barat, Kabupaten Raja Ampat - Findy Elsa Pratiwi; Ahmad Havid Jakiyudin; Muhamad Yusuf; Suparto Iribaram; Rachmad Surya Muhandy (Universitas Padjadjaran, 2023)
The Samsom tradition is a tribute to the spirits in certain areas located in Lilinta Village. This study aims to describe in a comprehensive manner about the implementation of the Samsom tradition and to find out the factors that influence the Samsom tradition that is still being maintained in Lilinta Village to this day. This study used a qualitative method with a social phenomenological paradigm. This study found that belief in spirits is a myth that grows up in Lilinta Village. Belief in existence and tribute spirits are performed with the aim of not interfering with human life. The Samsom tradition is a routine action in management of land. The tradition is performed to prevent dangers to the community which is part of the custom. It is an act of thought through experience that awakens people’s beliefs about offerings to spirits. The cultural shift is demonstrated by the displacement of some people from Lilinta Village to town. They are influenced by the lifestyle of people in Lilinta Village who are starting to distrust their ancestral traditions, so this tradition is only carried out by the older generation in Lilinta Village.